Political Marketing dalam Pemilihan Gubernur Sumatera Selatan Tahun 2018 (Studi Kasus Tim Pemenangan Herman Deru-Mawardi Yahya di Kota Palembang) - Anggi Septiyanti (Ampera: A Research Journal on Politics and Islamic Civilization, 2020)
The title of this research is "Political Marketing in Pilkada (Case Study: Victory of the Herman Deru-Mawardi Yahya Pair in the Election of the Governor of South Sumatra 2018 in the City of Palembang)". This study examines the phenomenon of political marketing as a strategy in a campaign. This paper elaborates and discusses how the political marketing process carried out by the successful team of the couple Herman Deru-Mawardi Yahya in Palembang City. The findings obtained from this study indicate that the political marketing process carried out by the success team of Herman Deru-Mawardi Yahya in Palembang City was very structured and managed to get the voice of the people of Palembang City. The political marketing process carried out by the success team of Herman Deru-Mawardi Yahya in the city of Palembang is first, showing the political products of this couple to the community such as spreading the vision and mission program of this couple to the entire Palembang City community. Secondly, to promote the people of Palembang City both through direct interaction and through print media, electronic media, and social media carried out directly by successful teams. Third, determine prices in the campaign, both in the campaign funding process and to build the price of the image of the couple. Fourth, the location of the campaign which was not only focused on one place but spread throughout the corner of the city of Palembang, because there was no major campaign in the city of Palembang.